2013
DOI: 10.1007/978-3-642-37765-5_3
|View full text |Cite
|
Sign up to set email alerts
|

The Antiviral Activities of Tetherin

Abstract: Tetherin (BST2/CD317) has emerged as a key host cell defense molecule, inhibiting the release and spread of diverse enveloped virions from infected cells. In this chapter, I review the molecular and cellular basis for tetherin's antiviral activities and the function of virally encoded countermeasures that disrupt its function. I further describe recent advances in our understanding of tetherin's associated role in viral pattern recognition and the evidence for its role in limiting viral pathogenesis in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
133
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(137 citation statements)
references
References 167 publications
4
133
0
Order By: Relevance
“…b-Actin was used as an internal control; primer sequence: 5¢-TTC CTG GGG ATG GAG TC-3¢ (forward); 5¢-CAG GTC TTT GCG GAT GTC-3¢ (reverse). Our data showed that both APOBEC3A/G, and tetherin, potent anti-HIV host factors, 17,[24][25][26] were significantly upregulated in MDMs treated exogenously with NTZ (Fig. 1F), supporting the belief that NTZ may be acting by limiting infection at early and late stages of the viral life cycle.…”
Section: Gekonge Bardin and Montanersupporting
confidence: 69%
See 1 more Smart Citation
“…b-Actin was used as an internal control; primer sequence: 5¢-TTC CTG GGG ATG GAG TC-3¢ (forward); 5¢-CAG GTC TTT GCG GAT GTC-3¢ (reverse). Our data showed that both APOBEC3A/G, and tetherin, potent anti-HIV host factors, 17,[24][25][26] were significantly upregulated in MDMs treated exogenously with NTZ (Fig. 1F), supporting the belief that NTZ may be acting by limiting infection at early and late stages of the viral life cycle.…”
Section: Gekonge Bardin and Montanersupporting
confidence: 69%
“…13,21,22 We analyzed the modulation of two known type I interferon-induced negative regulators of viral replication (ABOBEC 3G and tetherin [23][24][25][26][27][28] ) following 48-h incubation of MDM with 10 lg/ml NTZ. We utilized the following real-time reverse transcriptase polymerase chain reaction (RT-PCR) primers to characterize the expression of IFN-response genes following NTZ exposure, i.e., tetherin, primer sequence: 5¢-AAG AAA GTG GAG GAG CTT GAG G-3¢ (forward); 5¢-CCT GGT TTT CTC TTC TCA GTC G-3¢ (reverse), APOBEC3A, primer sequence: 5¢-TTC TTT GCA GTT GGA CCC GG-3¢ (forward); 5¢-CTC ATC TAG TCC ATC CCA GG-3¢ (reverse), and APOBEC3G, primer sequence: 5¢-TTA CCT GCT TCA CCT CCT GG-3¢ (forward); 5¢-TCA TCT AGT CCA TCC CAG GG-3¢ (reverse).…”
Section: Gekonge Bardin and Montanermentioning
confidence: 99%
“…The ability of tetherin to engage diverse families of enveloped viruses and the evolution of distinct mechanisms to counteract tetherin suggests that tetherin-mediated restriction does not require specific interactions between tetherin and viral proteins (22). Rather, it is the incorporation of tetherin into the viral and cellular membranes that is important.…”
mentioning
confidence: 99%
“…Each monomer consists of a continuous alpha helix arranged in parallel orientation, forming a coiled-coil dimer 14.5 to 16.5 nm in length (27)(28)(29)(30). Based on X-ray structures of the mammalian ectodomains, researchers have proposed two main models to predict how tetherin cross-links HIV-1 to the plasma membrane (22,31), with evidence to support both (see Fig. S1 in the supplemental material).…”
mentioning
confidence: 99%
“…Proteomics studies showed that a large number (ϳ100) of cellular proteins associated with the plasma membrane are incorporated into HIV-1 particles released by infected macrophages (21). However, the specific molecular mechanisms that mediate incorporation of host membrane proteins into virions remain largely unexplored, except for those for BST-2/tetherin (22) and virus receptors (23)(24)(25). This is in contrast to the incorporation of viral glycoproteins, where several mechanisms have been investigated (26,27).…”
mentioning
confidence: 99%